(untitled) (Law and Safety, 2021)
A comprehensive theoretical and legal study of the transformation of ideas about the nature of national security reform in domestic jurisprudence has been carried out. The author has defined the priorities and directions of the reform in the field of national security and, more importantly, its theoretical and methodological basis. It has been determined that the main object of the reform in the field of national security is the whole complex of public relations, which is subject to special protection by the system of entities of ensuring national security. The system of such social relations is centered around the defining national interests, which usually include the vital interests of a man, society and the state and the implementation of which ensures the state sovereignty, its progressive development, and safe living conditions and welfare of citizens. It has been noted that the main purpose of national security reform is to improve legislation and governance in the national security sector, which can provide qualitative strengthening in accordance with current and future needs of society to protect key national interests from external and internal real and potential threats. It has been concluded that national security is not considered in modern, both domestic and international science, exclusively as an “acquisition” and a sphere of monopoly responsibility of the state; we cannot eliminate the active participation of civil society structures, which should exercise public control over the course of such a reform and, if necessary, should have the tools of close communication with state authorities at the stage of initiating the reform, constructing its goals and objectives, directions and perspectives and at the stages of its implementation. Restriction of the capacity of the state, especially in times of economic crisis, highlights the need to optimize the participation of non-government actors in ensuring national security. Obviously, such activity of the non-governmental sector should be strongly encouraged by legislative instruments, legitimizing measures for national security reform through its close involvement and providing them with additional public support.